2015
DOI: 10.1016/j.joms.2015.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Maxillofacial Gunshot Injuries at an Urban Level I Trauma Center—10-Year Analysis

Abstract: Airway compromise was the most common life-threatening early problem. Patients admitted with higher stages of shock and lower mental status because of brain, vascular, and/or spinal cord injuries experienced prolonged hospitalization, increased treatment costs, and extended rehabilitation. Most of the facial GSWs presented as non-life-threatening injuries, but typically resulted in significant morbidity. The vast majority of injured patients relied on public aid or had no insurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
21
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 15 publications
3
21
0
2
Order By: Relevance
“…The patient presented in the case is another prime example of how a gunshot injury can represent a real challenge at the moment of trying to give an immediate and appropriate response. The patient that attended the medical service fell in an age above (25-30 years old average) what is reported in different studies of firearm injuries (2,6,10,11,(13)(14)(15). Regarding the sex, he fell in concordance of the majority of studies that mention that men have a higher prevalence of these types of injuries (3,5,6,10,11,13).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The patient presented in the case is another prime example of how a gunshot injury can represent a real challenge at the moment of trying to give an immediate and appropriate response. The patient that attended the medical service fell in an age above (25-30 years old average) what is reported in different studies of firearm injuries (2,6,10,11,(13)(14)(15). Regarding the sex, he fell in concordance of the majority of studies that mention that men have a higher prevalence of these types of injuries (3,5,6,10,11,13).…”
Section: Discussionmentioning
confidence: 79%
“…The patient that attended the medical service fell in an age above (25-30 years old average) what is reported in different studies of firearm injuries (2,6,10,11,(13)(14)(15). Regarding the sex, he fell in concordance of the majority of studies that mention that men have a higher prevalence of these types of injuries (3,5,6,10,11,13). It has been reported that regarding non intentional firearm injuries, those that happen by a rifle represent the lowest percentage, after handgun, and shotgun injuries (16); this gives the case a more interesting take on the rarity of these lesions.…”
Section: Discussionmentioning
confidence: 79%
“…Ancak özellikle baş-boyun bölgesinde oluşan savaş yaralanmalarında tedavinin zamanlaması ve tedavi/rekonstrüksiyon seçenekleri ile ilgili ortak bir fikir birliği bulunmamaktadır (2,17) . Bu tarz hastalar ile sık karşı-laşılmıyor olmasının beraberinde getirdiği kurumsal bilgi eksiklikleri nedeniyle tedavi seçenekleri merkezler ve hastalar arasında ciddi düzeyde farklılıklar gösterebilmektedir.…”
Section: Introductionunclassified
“…In a retrospective study about body wounds caused by war projectiles, 6.9% of injuries affected the face 1 . The majority of such maxillofacial gunshot wounds were caused by suicide attempts, mostly committed by young men 1 . In general, facial gunshot injuries have fatal results.…”
Section: Introductionmentioning
confidence: 99%